A STUDY AND MONITORING THE HYDROLOGICAL INDICATORS OF THE SEASONAL LAKE OF SHARI IN THE IRAQI SALAH AL-DIN PROVINCE AND THE POSSIBILITY OF USING THEM TO HARVEST WATER USING THE TECHNOLOGIES OF GIS AND RS - Dr. Aws Talak Mashaan, Dr. Zuhair Nawraz Yaseen (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The aim of the study is to find out the storage volume and the surface area of the reservoir as well as the perimeter and the area for each contour line, by analyzing the spatial variables of geomorphological phenomena at elected levels of the reservoir, and that the working method is imposed by the process of selecting the optimum level, which is the method that leads to the goal, by identifying seven different levels. It is the maximum lake height, as the study data was derived using the Digital Height Model (DEM), which is a digital file that shows the heights of the lands on a regular basis horizontally in the form of a set of points in the region, what is determined by their flat positions (Y. X) and their height (Z), origin It was conducted by the American NASA Research and Space Sciences agency on the SRTM radar satellite with a discriminatory accuracy of (12.5 × 12.5) m for the year (2011) which is high accuracy and appropriate for this study and its treatment using the (Arc GIS 10.4) program by adopting a separator Contour (1) meter .